2008
DOI: 10.1093/cercor/bhm248
|View full text |Cite
|
Sign up to set email alerts
|

Encoding, Rehearsal, and Recall in Signers and Speakers: Shared Network but Differential Engagement

Abstract: Short-term memory (STM), or the ability to hold verbal information in mind for a few seconds, is known to rely on the integrity of a frontoparietal network of areas. Here, we used functional magnetic resonance imaging to ask whether a similar network is engaged when verbal information is conveyed through a visuospatial language, American Sign Language, rather than speech. Deaf native signers and hearing native English speakers performed a verbal recall task, where they had to first encode a list of letters in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 57 publications
7
43
0
Order By: Relevance
“…Experimental studies have found differences in the verbal short term memory of deaf people, which may be due to the nature of sign language and/or different neural organization (Emmorey & Wilson, 2004;Rudner, Andin, & Ronnberg, 2009;Wilson & Emmorey, 1997). It is important for researchers who might want to use these norms to consider differences in articulation rates and phonological similarity for signs versus spoken words which may influence memory capacity, encoding and retrieval (see Wilson & Emmorey, 2000 for a review), and normative differences in memory for serially presented material in deaf people (Boutla, Supalla, Newport, & Bavelier, 2004), such as the tendency to show less temporal order effect in free recall tasks (Bavelier et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have found differences in the verbal short term memory of deaf people, which may be due to the nature of sign language and/or different neural organization (Emmorey & Wilson, 2004;Rudner, Andin, & Ronnberg, 2009;Wilson & Emmorey, 1997). It is important for researchers who might want to use these norms to consider differences in articulation rates and phonological similarity for signs versus spoken words which may influence memory capacity, encoding and retrieval (see Wilson & Emmorey, 2000 for a review), and normative differences in memory for serially presented material in deaf people (Boutla, Supalla, Newport, & Bavelier, 2004), such as the tendency to show less temporal order effect in free recall tasks (Bavelier et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A body of work has investigated working memory for sign language and found that although it is functionally similar to working memory for speech and supported by similar neural mechanisms, there are language modality specific differences in the neural networks that support working memory (for a review see Rudner, Andin & Rönnberg, 2009). In particular, working memory for sign language specifically recruits bilateral superior parietal regions associated with visuospatial processing (Bavelier, Newman, Working memory for manual gestures Mukherjerr, Hauser, Kemeny, Braun & Boutla, 2008;Rönnberg, Rudner & Ingvar, 2004;Rudner, Fransson, Nyberg, Ingvar & Rönnberg, 2007). This suggests that there are fundamental differences in the working memory processing of oral and gesture-based languages, despite considerable functional similarities Rudner et al, 2009;Rudner & Rönnberg, 2008).…”
Section: Working Memory For Manual Gestures 13mentioning
confidence: 99%
“…However it has also been suggested that modality specific activation of parietal cortex reflects language modality specific reliance on executive strategies during working memory tasks (Bavelier et al, 2008).…”
Section: Working Memory For Manual Gestures 13mentioning
confidence: 99%
“…This includes the inferior frontal gyrus (IFG) (classically called Broca's area), superior temporal sulcus (STS) and adjacent superior and middle temporal gyri, and the inferior parietal lobe (IPL) (classically called Wernicke's area) including the angular (AG) and supramarginal gyri (SMG) (4,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Likewise, narrative and discourse-level aspects of signed language depend largely on right STS regions, as they do for spoken language (17,19).…”
mentioning
confidence: 99%